Problematika Sarana Prasarana Berpengaruh Terhadap Proses Belajar Mengajar di Sekolah Dasar - Fitri, Aida; Ulfah, Haazimah; Aswita, Suci (Peneliti.net, 2024)
Facilities and infrastructure are important components in helping elementary school teachers and students with learning activities. Sufficient facilities and infrastructure can improve teaching standards and provide comfort for students while studying. In reality, there are still many elementary schools (SD) in Indonesia that lack infrastructure. This shows that although education in Indonesia continues to develop, there are still big challenges in meeting the basic needs of students, such as adequate learning facilities. The aim of this research is to specifically identify the level of appropriateness of facilities and infrastructure in elementary schools. This data can be used to prioritize solving infrastructure problems in elementary schools. Facilities and infrastructure have a big impact on how well students learn. This shows how important facilities and infrastructure are in supporting high-quality learning for students. Management of facilities and infrastructure is an activity that is very important for the success of the educational process in schools. Similar to management in general, managing facilities and infrastructure in schools requires a process that includes planning, organizing, mobilizing, maintaining and supervising. It is important to carefully plan what the school needs in terms of facilities and infrastructure that support all learning processes in the school.